ELECTROCARDIOGRAPHIC MANIFESTATIONS IN PAEDIATRIC WILSON DISEASE - Hamdani, Sara Batool; Cheema, Huma Arshad; Saeed, Anjum; Malik, Hassan Suleman; Sehar, Tayyaba (Journal of Ayub Medical College Abbottabad, 2017)
Background: Wilson disease (WD) is one of the most common metabolic liver diseases in older children. It has a strong genetic background with autosomal recessive inheritance. WD is a multisystem disorder with predominant hepatic and neurological manifestations and variable age of presentation. The data on cardiac manifestations in children is very limited and only few adult studies are available in the literature. This study was planned to determine the frequency and spectrum of Electrocardiographic (ECG) changes in pediatric WD. Methods: This was an observational cross-sectional study conducted at The Children Hospital & the Institute of Child Health, Lahore, from January 2015 to January 2017. The children diagnosed as Wilson disease were enrolled for the recording of resting ECG. The ECG changes were seen and discussed with an experienced pediatric cardiologist who was involved and explained about the objectives of study. Result: Total 55 patients were enrolled but record of ECG was missing for 4 patients and excluded from the study. Out of 51 patients 22 had at least one ECG abnormality. Most frequent findings seen were T wave abnormality in 18 patients (35.2%) followed by sinus tachycardia and sinus bradycardia in 12 and 8 patients respectively. Other abnormalities included bifid P waves, ST segment changes each of 2 patients, and one premature ventricular contraction. QRS details including axis, complex, amplitude ratio and QT interval was normal in all the patients. There was no mortality during the study period due to cardiac cause. Conclusion: ECG abnormalities are not uncommon in pediatric WD but of mild nature. These are presumably related to underlying cardiomyopathy due to deposition of copper in heart which can be quantified by cardiac magnetic resonance imaging (MRI) and echocardiography is required to confirm ECG abnormalities detected. Keyword: Wilson disease; ECG changes; cardiomyopathy